THE SEA OF OKHOTSK CRUST FROM DEEP SEISMIC SOUNDING DATA - Piip V.B.; Rodnikov A.G. (My University, 2004)
The crustal structure of the Sea of Okhotsk was investigated by way of reinterpreting the data obtained along 22 deep seismic sounding (DSS) profiles. Eight profiles traversed the Sea of Okhotsk. These seismic surveys were performed during the International Geophysical Year in 1958-1959 by the researchers from the Institute of the Physics of the Earth, USSR Academy of Sciences. Seven profiles were surveyed in 1963-1964 near the shores of Sakhalin Island by geophysicists from the Institute of the Physics of the Earth (USSR Academy of Sciences) and from the Sakhalin Multidisciplinary Research Institute. The new interpretation of the seismic data confirmed the earlier ideas of the reduced crustal thickness in the deep-sea basins of the Sea of Okhotsk, such as, the Kuril Basin, the Deryugin and Tinro basins, the sedimentary trough of the Tatar Strait, where the Moho surface showed low boundary velocities of seismic waves, not higher than 7.6-7.8 km s-1. It appears that the sedimentary basins of the Sea of Okhotsk reside above asthenospheric diapirs including magma chambers. A system of rifts and spreading centers was mapped in the northern and central parts of the Sea of Okhotsk, in the Tatar Strait, and in the Kuril Basin. Paleosubduction zones that had been active during the late Cretaceous and Early Paleogene time and are marked by ophiolite belts at the present time have been traced in the earth crust near the eastern shores of Sakhalin. Remnants of paleosubduction zones were mapped using seismic data in the Sea of Okhotsk along the Okhotsk-Chukotka volcanic belt, which seem to be the fragments of a lithospheric plate that had been going down under the active continental margin in Mesozoic time.
Keywords: DEEP SEISMIC SOUNDING; SEA OF OKHOTSK; CRUSTAL STRUCTURE; PALEOSUBDUCTION ZONES; Mesozoic; Paleogene; Cretaceous; Mesozoic; Cenozoic::Paleogene; Мезозой::Меловая; Мезозой; Кайнозой::Палеоген; Mesozoic::Cretaceous